2009
DOI: 10.1001/archdermatol.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Refractory Ulcerative Necrobiosis Lipoidica Diabeticorum With Infliximab

Abstract: Background: Necrobiosis lipoidica diabeticorum (NLD) is a rare, granulomatous inflammatory skin disease of unknown origin, sometimes associated with diabetes mellitus. Skin lesions usually develop on the lower extremities and can progress toward ulceration and scarring. Many treatments have been proposed, but few have demonstrated consistent efficacy, and no standard regimens have emerged to date. Observations: An 84-year-old woman with type 1 diabetes mellitus presented with a 3-year history of chronic right-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
(26 reference statements)
1
22
0
1
Order By: Relevance
“…Inhibition of such inflammatory agents will reduce or inhibit disease progression. Therapy with anti-TNFa drugs or antibodies was shown to improve insulin sensitivity and decrease cardiovascular risk index [14][15][16]. A substantial number of studies show that there are a number of signaling pathways involved in the regulation of inflammation, with nuclear factor-kappa B (NF-jB) being a key component.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of such inflammatory agents will reduce or inhibit disease progression. Therapy with anti-TNFa drugs or antibodies was shown to improve insulin sensitivity and decrease cardiovascular risk index [14][15][16]. A substantial number of studies show that there are a number of signaling pathways involved in the regulation of inflammation, with nuclear factor-kappa B (NF-jB) being a key component.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of these publications suggest that it may result from an important role of TNF-α in generation of granulomas and pathogenesis of NL [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors also suggest immunological disturbances leading to deposits of immunoglobulins in skin vessels and disturbances in platelet aggregation [8][9][10][11][12]. Recent literature data show that tumor necrosis factor α (TNF-α) inhibitors such as adalimumab, infliximab or etanercept are beneficial in treatment of recalcitrant cases of necrobiosis lipoidica, which probably results from the fact that TNF-α plays an important role in development of inflammation and granulomas in the course of NL [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A PubMed search about the treatment of NL with biological agents returned 6 previously reported cases in the English-language literature [19,20,21,22,23,24]. Clinical characteristics are summarized in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of NL was seen after the first month of treatment, and the lesion continued to resolve over the next 8 months. In 2009, Hu et al [23] reported complete healing in an 84-year-old woman with chronic ulcerated NL of her right lower extremity after 3 infusions of infliximab (5 mg/kg at weeks 0, 2 and 6). In 2009, Zhang et al [24] published the case of a 29-year-old woman with NL affecting her lower extremities and trunk successfully treated using 50 mg subcutaneous etanercept injections twice weekly for 3 months, then weekly after that.…”
Section: Discussionmentioning
confidence: 99%